2000
DOI: 10.1007/s001470050277
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment of hypercholesterolemia of renal transplant allograft recipients with fluvastatin and gemfibrozil

Abstract: The aim of this study was to investigate the safety and efficacy of combined treatment with fluvastatin (F) and gemfibrozil (G) in hypercholesterolemic renal transplant recipients (RTR). Ten hypercholesterolemic (total cholesterol [TC] > 220 mg/dl) RTR (7 men) with mean age 44 years (range 25-56 years) who remained hypercholesterolemic after 3 months of treatment (period A) with fluvastatin (40 mg/d) continued taking the same dose of F plus G (600 mg/dl) for another 3-month period (B). Serum total cholesterol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…20,21 Furthermore, it was indicated that combination fluvastatin-gemfibrozil treatment was safe and useful even in hypercholesterolemic renal transplant recipients. 22 Farnier et al 23 analyzed the data from 10 studies with a total of 1018 patients who received combination therapy of fluvastatin and a fibrate (ie, bezafibrate, fenofibrate, gemfibrozil) for primary hypercholesterolemia or mixed hyperlipidemia. They concluded that the combination of fluvastatin and fibrates had a complementary effect on lipid disorders, with no major safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Furthermore, it was indicated that combination fluvastatin-gemfibrozil treatment was safe and useful even in hypercholesterolemic renal transplant recipients. 22 Farnier et al 23 analyzed the data from 10 studies with a total of 1018 patients who received combination therapy of fluvastatin and a fibrate (ie, bezafibrate, fenofibrate, gemfibrozil) for primary hypercholesterolemia or mixed hyperlipidemia. They concluded that the combination of fluvastatin and fibrates had a complementary effect on lipid disorders, with no major safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…When given chronically to patients with dyslipidemias, PPAR α agonists, such as gemfibrozil, lower plasma triglycerides and increase high‐density lipoprotein cholesterol levels. Consequently, PPAR α agonists are widely prescribed for post‐transplant hyperlipidemia and appear entirely safe in such a setting [15–18]. In fact, therapy with PPAR α agonists may provide renoprotection from the damaging effects of chronic dyslipidemia [19].…”
Section: Discussionmentioning
confidence: 99%